A theoretical and experimental investigation of a solid desiccant air dehumidification system using shell-tube heat and mass exchanger configuration - Katili, Adrian Rosseno (2019)
The building sectors represent about 40% of total primary energy consumption and more than 30% of CO2 emissions globally. In hot and humid climates, the need for air conditioning for thermal comfort contributes to around 60% of domestic buildings energy consumption. This is aggravated by the widespread use of inefficient and energy intensive mechanical vapour compression air conditioning systems and the way air humidity is controlled. An extensive literature review of air dehumidification systems was conducted to map out the state of existing technology. This re-enforced the status of existing passive cooling technologies operating according to the principle of adsorption, absorption and evaporation as offering promising solutions but of limited performance. This research aims to investigate potential design enhancement of solid desiccant based air dehumidification systems that can extend the applicability of evaporative cooling systems to hot and humid regions. However, this requires overcoming the common problems associated with solid desiccant systems in regards to removing large amount of heat released during the adsorption process and residual heat from the regeneration process. Therefore, this thesis proposes an innovative solid desiccant air dehumidification system arranged in the form of a shell-tube heat and mass exchanger configuration. The proposed air dehumidification arrangement is designed to enhance both heat and mass transfer between the solid desiccant layer and its surrounding during the adsorption and regenerations process. The design incorporates a solid desiccant annular layer inside the heat exchanger tubes. A bundle of these desiccant filled tubes was enclosed in cylinder with two openings to form a tube-shell heat and mass exchanger. A rolled thin copper mesh was used to support the solid desiccant particles against the tube wall while allowing air to flow through the centre of the tube.